2022
DOI: 10.1101/2022.11.20.517205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Novel Machine Learning Method for Mutational Analysis to Identifying Driver Genes in Breast Cancer

Abstract: Breast cancer has emerged as a severe public health issue and one of the main reasons for cancer-related mortality in women worldwide. Although the definitive reason for breast cancer is unknown, many genes and mutations in these genes associated with breast cancer have been identified using developed methods. The recurrence of a mutation in patients is a highly used feature for finding driver mutations. However, for various reasons, some mutations are more likely to arise than others. Sequencing analysis has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Abnormal activation of this pathway, particularly through EGFR activation, is highly prevalent [27]. Ras proteins, central to this pathway, are frequently implicated in oncogenesis, with their mutations associated with cancer development [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Abnormal activation of this pathway, particularly through EGFR activation, is highly prevalent [27]. Ras proteins, central to this pathway, are frequently implicated in oncogenesis, with their mutations associated with cancer development [28].…”
Section: Resultsmentioning
confidence: 99%
“…PI3K/Akt signaling pathway: The EGFR-mediated signaling pathway includes the PI3K/AKT pathway, which is frequently dysregulated in various human malignancies [28]. Extensive research has shown that PI3Ks are crucial in regulating essential cellular processes involved in cancer development, including metabolism, cell survival, proliferation, differentiation, and motility [28].…”
Section: Mapk Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation